Simulations of the Atmospheric Boundary Layer in a Wind Tunnel with Short Test Section - Luciana Bassi Marinho Pires; Igor Braga de Paula; Gilberto Fisch; Ralf Gielow; Roberto da Mota Girardi (Journal of Aerospace Technology and Management, 2013)
http://dx.doi.org/10.5028/jatm.v5i3.190